Pectin Oligosaccharides Ameliorate Colon Cancer by Regulating Oxidative Stress- and Inflammation-Activated Signaling Pathways - Tan, Haidong; Chen, Wei; Liu, Qishun; Yang, Guojun; Li, Kuikui (Frontiers in Immunology, 2018)
Colon cancer (CC) is the third most common malignancy worldwide and it is still a big challenge for exploring new effective medicine for treating CC. Natural product promoting human health has become a hot topic and attracted many researchers recently. Pectin, a versatile polysaccharide in plant cell wall, mainly consists of four major types of polysaccharides: homogalacturonan (HG), xylogalacturonan (XGA), rhamnogalacturonan I (RGI) and II (RGII), all of which can be degraded into various pectin oligosaccharides (POS) and may provide abundant resource for exploring potential anti-cancer drugs. POS have been regarded as a novel class of potential functional food with multiple health-promoting properties. POS have antibacterial activities against some aggressive and recurrent bacterial infection, and exert beneficial immunomodulation for controlling CC risk. However, the molecular functional role of POS in the prevention of CC risk and progression remains doubtful. The review focuses on antioxidant and anti-inflammatory roles of POS for promoting human health by regulating some potential oxidative and inflammation-activated signaling pathways, including adenosine monophosphate–activated protein kinase (AMPK), the transcription factor nuclear factor erythroid-2-related factor-2 (Nrf2), and transcription factor nuclear factor-κB (NF-κB) pathways. The activation of these signaling pathways increases the antioxidant and anti-inflammatory properties, which will result in the apoptosis of CC cells or in the prevention of CC risk and progression. Thus, POS may inhibit CC development by affecting antioxidant and anti-inflammatory signaling pathways AMPK, Nrf2 and NF-kB. However, POS also can activate signal transduction and transcriptional activator 1 (STAT1) and 3 signaling pathway, which will reduce antioxidant and anti-inflammatory properties and promote CC progression. Specific structural and structurally modified POS may be associated with their functions and should be deeply explored in the future. The present review paper lacks the important information for the linkage between the structure of POS and its function. To further explore the effects of prebiotic potential of POS and their derivatives on human immunomodulation in the prevention of CC, the specific POS with a certain degree of polymerization or purified polymers are highly demanded to be performed in clinical practice.